Moderate potassium lowering effect of exogenous atrial natriuretic peptide in patients with acute heart failure. Issue 6 (December 2021) - Konishi, Masaaki; Akiyama, Eiichi; Shibata, Atsushi; Kida, Keisuke; Ishii, Shunsuke; Ikari, Yuji; Kimura, Kazuo; Tamura, Kouichi; Matsumoto, Shingo
Highlights: Exogenous atrial natriuretic peptide lowered potassium level in acute heart failure. Changes in potassium were correlated with urine volume. Risk of hypokalemia was low unless treated with additional furosemide. Abstract: Background Recent data suggest that the angiotensin receptor neprilysin inhibitor modulates plasma levels of natriuretic peptides and attenuates the risk of hyperkalemia in patients with heart failure (HF). However, the impact of natriuretic peptides on serum electrolyte abnormalities, especially abnormalities in sodium and potassium levels in patients with HF remains unclear. Methods We performed a post-hoc analysis of a multicenter prospective cohort study in 162 patients with acute HF (74.2 ± 13.3 years, 64.2% male, left ventricular ejection fraction 44 ± 15%) treated with intravenous carperitide, an exogenous atrial natriuretic peptide. Results The dose of carperitide was correlated with urine volume (σ = 0.205, p = 0.009), suggesting a significant diuretic effect. During the initial 48 h, serum sodium level remained unchanged both in 53 patients with carperitide alone (from 140 ± 4 to 140 ± 3 mEq/L, p = 0.653) and 109 patients treated with a combination of carperitide and furosemide (141 ± 4 to 141 ± 4 mEq/L, p = 0.644). On the contrary, serum potassium level was decreased both in patients with carperitide alone (from 4.32 ± 0.70 to 4.08 ± 0.47 mEq/L, p = 0.004) and patients treated with a combination of carperitide and furosemide (4.17 ± 0.55 to 3.98 ± 0.47, p < 0.001), with a significant association between urine volume and change in potassium level in patients treated with carperitide alone (σ = -0.313, p = 0.023). The incidence of hypokalemia at 24 h was higher in patients treated with 20 mg furosemide or more (12.5% vs. 2.8%, p = 0.039). Conclusions Serum potassium level decreased after HF treatment with exogenous atrial natriuretic peptide, with a significant correlation to urine volume. The risk of hypokalemia was low, unless treated with additional furosemide. Graphical abstract: Image, graphical abstract